Niche modelling and comparative morphology untangle taxonomy of the Dysschema eurocilia clade (Lepidoptera: Erebidae) and reveal a relictual Pleistocene Arc distribution. Issue 1 (31st December 2022) - Moraes, Simeão de Souza; Gueratto, Patrícia Eyng; Dos Santos, Jessie Pereira; Santos, Mateus Henrique; Freitas, André Victor Lucci; Duarte, Marcelo
Abstract : Dysschema is the largest genus in Pericopina, with 69 species. The highly polymorphic species D. eurocilia (Cramer, 1777 ) was recently united in a clade with three other species: D. aorsa (Boisduval, 1870 ) stat. rev., D. bivittata (Walker, 1854 ) stat. rev. and D. molesta (Hering, 1925 ) stat. rev. Typological taxonomic treatment and lack of understanding of geographic distributions contributed to a proliferation of publications and disputed validity of names. We analysed the genital morphology and wing patterns for the four putative species in the ' D. eurocilia clade' and estimated the ecological niche using Ecological Niche Modelling (ENM) to clarify taxonomic scenarios, delimit species and infer speciation mechanisms. We also used ENM to understand the distributions of phenotypes of D. eurocilia . The morphological data and ENM suggested an alternative hypothesis to previous taxonomic works on species within the ' D. eurocilia clade'. The ENM also revealed distribution patterns supporting the northern Andes as a geographic barrier between Central and South America, while the interconnected Andean valleys might represent areas of sympatry. Additionally, the predicted distribution showed that certain phenotypes in D. eurocilia have distribution through the South American diagonal of open formations, which might represent a relictual distribution known as the Pleistocene Arc.